New insights into the role of macrophages in cancer immunotherapy - Zhou, Li; Zhao, Tiantian; Zhang, Ruzhe; Chen, Chen; Li, Jiwei (Frontiers in Immunology, 2024)
Macrophages are the main component of the tumor microenvironment, which are differentiated from monocytes in the blood and play an important role in cancer development. Tumor associated macrophages (TAMs) can promote tumor growth, invasion, metastasis and resistance to anti-PD-1 therapy by regulating PD-L1 expression and interacting with other immune cells in the tumor microenvironment. However, when activated properly, macrophages can also play an anti-tumor role by enhancing the phagocytosis and cytotoxicity of tumor cells. TAM is associated with poor prognosis and drug resistance in patients treated with immunotherapy, indicating that macrophages are attractive targets for combined therapy in cancer treatment.Combination of targeting TAMs and immunotherapy overcome the drug resistance and achieved excellent results in some cancers, which may be a promising strategy for cancer treatment in the future. Herein, we review the recent findings on the role of macrophages in tumor development, metastasis and immunotherapy. We focus mainly on macrophage-centered therapy, including strategies to deplete and reprogram TAMs, which represent the potential targets for improving tumor immunotherapy efficacy.